INTEGRATING STRUCTURE AND LIGAND-BASED APPROACHES FOR MODELLING THE HISTONE DEACETYLASE INHIBITION ACTIVITY OF HYDROXAMIC ACID DERIVATIVES - Pham-the, Hai; Le-thi-thu, Huong (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Structure and ligand-based drug design approaches have be been integrated to accurately predict the inhibition activity of hydroxamic acid (HA) derivatives against the histone deacetylase-2 enzyme (HDAC2). Methods: The active conformationsâ€ of the ligands in the binding site of the enzyme were determined by docking assays. More than 1000 0â€“3 dimensional molecular descriptors included in Dragon package were calculated and utilized for developing quantitative structure-activity relationship (QSAR) models through a multiple linear regression approach coupled with the genetic algorithm (GA-MLR). Results: The final model obtained showed suitable robustness and stability, with low correlation between descriptors and good predictive power. QSAR model was then used for screening bioactivity from a series of 36 novel HAs and found five candidates with very good bioactivity (half maximal inhibitory concentration<0.1 Î¼M). Docking experiment revealed the binding mode of these compounds into the active site of HDAC2. Drug-likeness and toxicity profiles of the compounds were checked through chemoinformatics tools. Conclusion: The results from this study can lead to rational design and synthesis of highly selective and potent HDAC2 inhibitors.